Long-snouted seahorse, Hippocampus guttulatus, under global warming - Costa, Ana B. (2022)
The earth’s climate system and the global ocean have been warming up, since the mid-twentieth century and it is expected that the global and ocean´s temperature will rise in the next years even more [1,2,13,25,28]. For ectotherms, such as fish, temperature is a determinant cue for several behavioural [29], physiological [24], and metabolic processes [6]. Seahorses’ particular life history makes them vulnerable to human or natural disturbances [17]. The long snout seahorse, Hippocampus guttulatus, is one of the two species that inhabit the coastal areas of Portugal [23]. The present study aims to assess the effects of ocean warming on growth, feed intake and behavior patterns of adult H. guttulatus. Results provide clear evidence of detrimental effects of exposure to warming on this species. Under extreme temperatures (24ºC), the increased food ingestion was not enough for fish to support growth (weighted less), which suggests that fish were spending energy to counterbalance the thermal stress they were exposed to. Fish under both elevated temperature treatments (20 and 24ºC) were also spending more energy in active behaviours. Altogether, these data may indicate that ocean warming will have a drastic effect on seahorse populations currently inhabiting the Sado estuary.